A Comparative Pharmaceutical Study of Mandura Bhasma (Iron Oxide-Based Powder Medicine) Prepared by Two Different Methods (AYUSHDHARA, 2025)
In Ayurveda, drugs are basically derived from plant, animal, and mineral origins. Rasa shastra is unique branch of Ayurveda which mainly deals with drugs having metals and mineral origin. Apart from herbal medicines, metal and mineral-based drugs have gained popularity due to their rapid action in very low doses and their long shelf life. However, the primary challenge is to convert metals and minerals origin drugs into absorbable and assimilable forms. so, that the drugs not produce any ill effect over body system. In order to overcome this problem raw metals and minerals are changed into an organo-metallic assimilable form known as Bhasma. The process by which metals and minerals drugs converted into Herbo-minerals forms called Bhasmikarana. Mandura is an important iron oxide-based drug used for management of various ailments as described in various Ayurvedic texts. The preparation of Mandura Bhasma involves three main processes, namely Shodhana (purification) process, Bhavana (trituration), Marana (incineration) process. There are lots of process described in ayurvedic text but little research work was done to know the methods that are highly valuable. Now current needs are to adopt such methods for drugs preparation which is cheap, safe, efficient that can be easily available to the common peoples. In current study two methods were employed for the preparation of Mandura Bhasma and analytical study was performed to compare the best methods among them with reference to quality, efficacy and safety.